Analysis of Investor Perceptions on the Relationship between Foreign Direct Investment and Bribery in Thailand - Chanchanoke, Chennarong (2024)
Bribery within Thailand's investment process poses significant challenges for Foreign Direct Investment (FDI), which plays a crucial role in the country's economic development. This study investigates how bribery and corruption affect investor perceptions and decisions, focusing on the interaction between FDI, bribery, and governance. By integrating theories of FDI, Corruption, Bribery, Good Governance, Public Service Motivation (PSM), and Social Value Orientation (SVO), the research explores strategies to enhance Thailand's investment climate. A mixed methods approach was employed. In the quantitative phase, a sample of 400 companies was analyzed using Structural Equation Modeling (SEM) to assess the relationships between key factors influencing FDI, such as economic growth, infrastructure, political stability, and the efficiency of government processes. The qualitative phase involved semi-structured interviews with 15 key informants, including businessmen, investors, and anti-bribery experts. Interviews continued until data saturation was reached, ensuring comprehensive insights. The research findings indicate that economic growth, infrastructure, and political stability are critical determinants of FDI, with corruption and bureaucratic inefficiencies acting as significant barriers. Investors report that bribery plays a prominent role in securing public contracts, accelerating government processes, and bypassing regulatory obstacles, undermining fair competition and public service quality. Despite existing anti-bribery laws, enforcement remains inconsistent, and inadequate legal protections deter whistleblowing. Based on the findings, the study recommends strengthening anti-corruption measures through enhanced law enforcement and promoting digital transformation to improve government transparency and efficiency. Additionally, policymakers should focus on increasing public awareness of anti-bribery laws, developing robust monitoring and evaluation mechanisms, and offering better legal protections for whistleblowers. Promoting Public Service Motivation (PSM) and Social Value Orientation (SVO) within the business sector can further foster ethical practices and reduce corruption. International collaboration and digital reforms, inspired by models such as Singapore, are critical to building a more transparent and investment-friendly environment in Thailand.